Changes in stratospheric composition, chemistry, radiation and climate caused by volcanic eruptions - Grainger, R; Highwood, E (2003)
The primary effect of a volcanic eruption is to alter the composition of the stratosphere by the direct injection of ash and gases. On average, there is a stratospherically significant volcanic eruption about every 5.5 years. The principal effect of such an eruption is the enhancement of stratospheric sulphuric acid aerosol through the oxidation and condensation of the oxidation product H2SO4. Following the formation of the enhanced aerosol layer, observations have shown a reduction in the amount of direct radiation reaching the ground and a concomitant increase in diffuse radiation. This is associated with an increase in stratospheric temperature and a decrease in global mean surface temperature (although the spatial pattern of temperature changes is complex). In addition, the enhanced aerosol layer increases heterogeneous processing, and this reduces the levels of active nitrogen in the lower stratosphere. This in turn gives rise to either a decrease or an increase in stratospheric ozone levels, depending on the level of chlorine loading.